PENERAPAN SANKSI PIDANA ADAT BAGI PELAKU PENCURIAN MENURUT HUKUM ISLAM DAN POSITIF - Khairilina (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2020)
Theft is one of the wrongdoings, which is strictly prohibited either by shari'ah, positive written law or unwritten customary law, because the act is detrimental to the lives of others. The purpose of this research is to look for answers to the main problem, namely how the customary law of Village in Aceh in solving theft, is the punishment of theft applied by Village traditional leaders in Indrajaya Pidie District in accordance with Islamic law. To answer these questions, the authors use the method of library research and field research through interview research techniques. The sample of the author's research is the village. The results showed that in the Villages in Indrajaya in resolving theft cases put forward traditional law. Settlement of theft disputes through deliberation, justice, promoting honesty, and not taking sides with either party. If the theft is committed by the children, the person responsible is the child's parents. If the theft is below the value of 1,000,000 (one million rupiahs), then it is resolved in the traditional village, which has various types of sanctions, whether in the form of advice, reprimands, compensation, statements of apology in front of the crowd at the Small Park or Mosque, ostracized by the village community, revocation of customary titles, as well as referrals. If the theft is above 10,000,000 (ten million rupiah), it will be taken to the police.